Plan de marketing para la creación de un complejo turístico en la ciudad de Quevedo período 2009-2010 127 p. - Pinyui Garcia, Yadira Cecibel (2010)
summary of the Plan as a whole. It includes the definition of the product that it is intended to market, detailing the differential advantage that it has over other similar products of the competition and how it is expected to maintain it; the necessary investment, both at the beginning and through time and the expected results, expressed in figures of return on investment, sales, profit, market share, etc ... The executive summary is very important when you want to obtain resources for the execution of the project. You must therefore summarize the entire Marketing Plan in a few paragraphs, at most in a few pages; making it clear that the subject has been studied seriously and deeply and that the proposal has a future and reasonable chances of success. www.monografías.com .- Your relationship is not directly related to the level of importance, since in a small number of pages you must indicate an excerpt from the content